Energy content of sublittoral biologically-relevant resources in the East Antarctic seas - Yu. G. Giginyak; Dz. A. Lukashanets; O. I. Borodin; V. E. Miamin; V. M. Baichorov (Ukrainian Antarctic Journal, 2019)
Objective.To determine the energy value of several groups of the East Antarctic sea biota and identify potential calorific differences in the context of both taxa and ecological groups. Methodology. Sampling was carried out by traditional methods (benthic traps, diving gathering), and remote sampling was also applied (using remote-controlled underwater vehicles). The energy value of organisms is determined using wet burning methods. Results. The energy indicators of the main biological objects of the sublittoral of the three seas at the East Antarctica were determined for the first time. It has been shown that in the studied sublittoral regions of the Cosmonauts, Cooperation (more Sodruzhestva) and Davis seas, the dominant species of marine zoobenthos was the sea urchin Sterechinus neumayeri (Meissner, 1900). The caloric values of starfish, polychaetes, nemerteans, sponges, ascidia, holothurians, crustaceans, and some other taxa of marine biota were determined. It is shown that the content of organic matter in Antarctic species varies from 12—94%, and caloric content — from 0.7—7.3% cal / mg dry matter, with the maximum values registered for amphipods and calanoids. The energy equivalents of marine zoobenthos per unit of bottom square have been calculated. The ratio equation of the caloric content of the substance of the studied object to the ashcontent is calculated. Conclusions. In general, we can conclude that the caloric values of marine zoobenthos in all three studied seas are close to each other. Furthermore, the caloric content of individual representatives of marine fauna varies significantly and, in general, depends on the quantity and quality of organic matter in certain species as well as on the season of year. The low-caloric representatives of the Antarctic flora and fauna correspond to the high substance ash levels of their body. Depending on the energy value significance, several groups of marine biota were represented, represented by various taxa.